The happiness index why today's employee emotions equal tomorrow's business success - Phelan, Matt (Ascent Audio, 2024)
In The Happiness Index: Why Today's Employee Emotions Equal Tomorrow's Business Success, cofounder and CEO of The Happiness Index Matthew Phelan delivers a fascinating dive into data from over 100 countries and 2 million human beings that helps us understand what really drives our engagement and happiness at work. In the book, you'll learn that "engagement" is what our brains need, and "happiness" is what our hearts need. A simultaneously inspirational and hands-on treatment of a subject of singular importance to everyone in the working world, The Happiness Index will benefit executives, managers, and other business leaders, as well as founders, business owners, and anyone else interested in helping the people around them flourish.